INTEGRATING SYNCHRONIZED TRANSLATION METHODS INTO ENGLISH LANGUAGE LEARNING IN ACADEMIC LYCEUMS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Students speak Uzbek from birth and this helps them easily master a number of academic subjects, while English is one of the most difficult languages for them to master. Of course, any new subject arouses interest among students and English is no exception, but over time it begins to disappear due to the amount of material for memorization that any oral subject involves and here, too, English is no exception, but the problem is that students study the main school subjects in their native language, and in our case, they study both the subject and the new language.